Uniportal video-assisted thoracic surgery colorectal lung metastasectomy in non-intubated anesthesia - Ambrogi, Vincenzo; Sellitri, Francesco; Perroni, Gianluca; Schillaci, Orazio; Mineo, Tommaso Claudio (Journal of Thoracic Disease; Vol 9, No 2 (February 28, 2017): Journal of Thoracic Disease, 2017)
Background: More than ten years ago we started a program of video-assisted thoracic surgery (VATS) lung metastasectomy in non-intubated local anesthesia. In this study we investigated the effectiveness and long term results of this combined surgical-anesthesiological technique. Methods: Between 2005 and 2014, 48 patients (25 men and 23 women) with pulmonary oligometastases from colorectal cancer, at the first episode, underwent VATS metastasectomy under non-intubated local anesthesia. Three patients required intubation for intolerance. In the same period 13 patients scheduled for non-intubated metastasectomy refused awake surgery and were used as a control group. Results: The two groups were homogeneous for both demographic and pathological features. Mean number of lesions resected per patient were 1.51 (non-intubated) vs. 1.77 (control), respectively (P=0.1). The oxygenation was significantly lower in the non-intubated group especially at the end of the procedure, but the values inverted from the first postoperative hour. There was no mortality in any groups. The non-intubated group demonstrated a significant shorter overall operating time (P=0.04), better quality of recovery after both 24 (P=0.04) and 48 hours (P=0.04), shorter median hospital stay (P=0.03) and lower estimated costs (P=0.03), even excluding the hospital stay. Major morbidity rate was lower (6% vs. 23%) yet not significant (P=0.1). Both disease free survival and overall survival were similar between groups. Conclusions: VATS lung metastasectomy in non-intubated local anesthesia was safely performed in selected patients with oligometastases with significant advantages in overall operative time, hospital stay and economical costs. Morbidity rate was lower yet not significant. Long term results were similar.